The role of parent-adolescent relationship quality and callous-unemotional traits on sexual prejudice in adolescence - Bruckner, Raffael; Schuster, Sarah; Hutzler, Florian (Frontiers in Developmental Psychology, 2024)
Sexual prejudice negatively impacts our society and commonly manifests itself in hostile attitudes and aggressive behaviour towards people who identify with the LGBTQIA+ community. Adolescents in particular are vulnerable to such negative world views. The present study investigated the impact of the parent-adolescent relationship quality, the potentially associated manifestation of psychopathic personality traits -so-called callous-unemotional (CU) traits -and their relation to sexual prejudice antigay hostility in adolescence. We observed that poor maternal relationship quality in terms of poor communication, lack of trust, and alienation is associated with selfish, cold-hearted personality traits. Moreover, we observed an indirect effect of CU-traits mediating the link between maternal relationship quality and antigay hostile attitudes and behaviour. Our findings emphasise the crucial role of attachment in the development of a child's affective personality.